EXPRESSIVE SPEECH ACTS IN ENGLISH: LINGUISTIC FEATURES AND COMMUNICATIVE FUNCTIONS (International journal of artificial intelligence, 2026)
Language is not only a tool for conveying information but also a means of expressing human emotions, attitudes, and psychological states. In pragmatics, this function of language is studied through the theory of speech acts. Among various types of speech acts, expressive speech acts occupy a special place, as they reflect the speaker’s inner feelings and emotional reactions. This article explores the nature of expressive speech acts in English, their main types, and their communicative significance.